Challenge, Change and Response: Research into Education in a Globalized Perspective - Xiang, Jing; Yan, Ying (International Dialogues on Education Journal, 2020)
Economic globalization not only brings opportunities to all countries in the world, but also brings crises and challenges. The solutions to crises and challenges also entrust education different missions. To this end, there is an urgent need to re-examine the purpose of education, to update the means of education and to change the role of education in order to respond to the logic of history, cultural orientation and the demands of the times, in accordance with the concept of equitable, viable and sustainable human and social development. Mainly from the 1970s, the education concept changes from lifelong education to the learning society. In the 1980s, the educational means from information technology into the virtual class, and then in the 1990s, the educational role with the economic globalization to the trade of educational service. Entering the 21st Century, the mode of educational development was from the Millennium goals to the sustainable development. The goal of sustainable development of human society depends on the sustainable development of education. The sustainable development of future education rests on the implementation of comprehensive, inclusive, just and quality education to ensure that all people have the opportunity to learn for life.